2000
DOI: 10.1016/s1095-6433(00)00241-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate measures in blind cave crayfish during environmental disturbances and social interactions

Abstract: Most animals continually assess the environment in which they live and alter their behavior according to various stimuli. As an observer, one looks for changes in a behavior indicating that an animal responded to a particular event. When the animal does not make significant behavioral changes as measured by bodily movements, the animal may be characterized as unresponsive to a given stimulus. This study demonstrates that when behavioral body movements can not be observed an internal physiological measure of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…More specifically, bradycardia or reversible heart arrests have been reported in crabs, lobsters and crayfish to a variety of optical and tactile stimuli (Cuadras, 1980;Cumberlidge and Uglow, 1977;Florey and Kriebel, 1974;Grober, 1990a;Grober, 1990b;Larimer and Tindel, 1966;McMahon and Wilkens, 1972;Mislin, 1966;Shuranova and Burmistrov, 2002;Uglow, 1973;Wilkens et al, 1974). Furthermore, another set of results also gathered in crustacea have shown that even though no observable behavioral responses were elicited, heart rate was measurably affected by small disturbances in the environment or by social interaction (Li et al, 2000;Listerman et al, 2000;Schapker et al, 2002). Given the remarkable sensitivity of this parameter to a variety of sensory modalities it has been posed that the cardiac response can serve as an indicator of perception in decapod crustaceans and could well be utilized in studies on perceptual physiology.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…More specifically, bradycardia or reversible heart arrests have been reported in crabs, lobsters and crayfish to a variety of optical and tactile stimuli (Cuadras, 1980;Cumberlidge and Uglow, 1977;Florey and Kriebel, 1974;Grober, 1990a;Grober, 1990b;Larimer and Tindel, 1966;McMahon and Wilkens, 1972;Mislin, 1966;Shuranova and Burmistrov, 2002;Uglow, 1973;Wilkens et al, 1974). Furthermore, another set of results also gathered in crustacea have shown that even though no observable behavioral responses were elicited, heart rate was measurably affected by small disturbances in the environment or by social interaction (Li et al, 2000;Listerman et al, 2000;Schapker et al, 2002). Given the remarkable sensitivity of this parameter to a variety of sensory modalities it has been posed that the cardiac response can serve as an indicator of perception in decapod crustaceans and could well be utilized in studies on perceptual physiology.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, by only monitoring the animal through external observation one can be misled in determining if an animal senses an environmental cue when its conduct remains unaffected. Measuring an index of internal state may provide additional information about the perception of a stimulus (Li et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it also needs to be noted that the oscillation of the pump that powers the IPOCAMP™ creates a slight pulse in water density that is vaguely evident in the signal received by the heartbeat sensor and this may explain some of these anomalies. Minor fluctuations in the cardiac activity of crustaceans have been previously observed in response to small reverberations within a water body [35].…”
Section: Cardiac Activity As a Measure Of Stressmentioning
confidence: 86%
“…Such tail tucking is also seen as a defense posture . These behaviors have been readily observed in the field and in laboratory settings (Bovbjerg, 1953(Bovbjerg, , 1956Bruski and Dunham, 1987;Li et al, 2000;Listerman et al, 2000). Interestingly, the behavioral postures noted in lobsters (Livingstone et al, 1980) are reversed for 5-HT and octopamine injections in the Australian crayfish, Cherax destructor (McRae, 1996).…”
Section: Measuring Synaptic Responsesmentioning
confidence: 92%